Changing our Thinking: Empirical Research on Law Student Wellbeing, Thinking Styles and the Law Curriculum - Molly Townes O'Brien; Stephen Tang; Kath Hall (Legal Education Review)
In 2010 six Threshold Learning Outcomes (TLOs) for law were developed by the Australian Learning and Teaching Council’s Discipline Scholars: Law. One of the TLOs concerns selfmanagement. This paper considers the importance of this TLO for legal education in the context of recent research which has established elevated levels of psychological distress in law students. The paper offers a conceptual framework centred on student engagement for intentional curriculum design in relation to the implementation of the self-management TLO. It also suggests some practical strategies for implementing this TLO through the adoption of approaches focused on supporting student autonomy and reflective practice.